Depression is associated with some patient‐perceived cosmetic changes, but not with radiotherapy‐induced late toxicity, in long‐term breast cancer survivors. Issue 3 (7th February 2012) - Brunault, Paul; Suzanne, Isabelle; Trzepidur‐Edom, Magdalena; Garaud, Pascal; Calais, Gilles; Toledano, Alain; Camus, Vincent
Abstract Objective Although depression is prevalent in long‐term breast cancer survivors (LTBCS; ≥5 years since diagnosis), it is underdiagnosed and undertreated. A better understanding of factors associated with depression could improve depression screening, treatment, and prevention in this population. Our study aimed to assess the link between patient and doctor ratings of breast cosmetic outcomes, late radiotherapy toxicity, and depression in LTBCS. Methods In all, 214 patients recruited from the ARCOSEIN study were assessed for late radiotherapy toxicity (by using the LENT‐SOMA scale) and patient and doctor ratings of breast cosmetic outcomes (mean = 6.7 years since the end of treatment). We reassessed 120 of these patients for depression (HAD) during a second wave of long‐term assessment (mean = 8.1 years since the end of treatment). We used univariate analyses and polytomous logistic regression analyses to predict the HAD depression, which was defined as follows: normal, 0–7 points; and significant depression, ≥8 points (8–10 points, possible depression; ≥11 points, probable depression). Results The mean HAD depression score was 4.5 ± 3.6. 19. 2% of our population had significant depression, 6.7% with probable depression, and 12.5% with possible depression. Significant depression was not associated with late radiotherapy toxicity or initial cancer‐related variables. Patients with probable depression reported worse cosmetic outcomes than nondepressed patients in terms of perceived breast largeness (p = 0.04), breast deformation (p = 0.02), and changes in skin pigmentation (p = 0.03). Conclusions In LTBCS, depression seems to be more strongly associated with changes in some patients' perceived breast cosmetic outcome than late treatment toxicity or initial cancer‐related variables. Copyright © 2012 John Wiley & Sons, Ltd.